Pembuatan Website Perpustakaan Institut Teknologi Padang - Arnas, Nadia Assyfa; Rahmah, Elva (Ilmu Informasi Perpustakaan dan Kearsipan, 2016)
This paper discussed about the creation of the Institute of Technology Padang Library website. This paper aims to describe how to manufacture Padang Institute of Technology Library website.The method used is descriptive method with data collection through observation or direct observation to the Library Institute of Technology Padang, interviews, and literature. From observations and interviews conducted in the library Institute of Technology Padang then collected some data as material to design websites that serve as a media campaign Padang Institute of Technology Library. Based on the discussion in the creation of websites in the Library of the Institute of Technology of Padang, we can conclude the following matters. First, the technology has become so prominent in all fields, as well as a library. Second, the design of this website is static application using CodeIgniter Framework (CI), which is one of the specially designed software in designing a simple website and install a local web server as a liaison and support in making a website using Wamp Server.Keyword: website, Â library, Institute of Technology Padang